2014
DOI: 10.1016/j.cmet.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Glutarylation Is a Protein Posttranslational Modification Regulated by SIRT5

Abstract: We report the identification and characterization of a five-carbon protein post-translational modification (PTM) called lysine glutarylation (Kglu). This protein modification was detected by immunoblot and mass spectrometry (MS), and then comprehensively validated by chemical and biochemical methods. We demonstrated that the previously annotated deacetylase, sirtuin 5 (SIRT5), is a lysine deglutarylase. Proteome-wide analysis identified 683 Kglu sites in 191 proteins and showed Kglu is highly enriched on metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
795
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 687 publications
(844 citation statements)
references
References 44 publications
17
795
1
1
Order By: Relevance
“…The preference of SIRT5 for negatively charged acyl groups was further corroborated by another recent study (156). Tan et al identified and validated lysine glutarylation as an evolutionary conserved posttranslational modification; similar to lysine succinylation, this modification was also regulated by SIRT5 (156). Proteomic screening of liver extracts from Sirt5 KO mice revealed hyperglutarylation of 683 lysine sites on 191 proteins; more than three quarters of these proteins were found to be mitochondrial (156).…”
Section: Sirt5 and Protein Deacylationsupporting
confidence: 51%
See 4 more Smart Citations
“…The preference of SIRT5 for negatively charged acyl groups was further corroborated by another recent study (156). Tan et al identified and validated lysine glutarylation as an evolutionary conserved posttranslational modification; similar to lysine succinylation, this modification was also regulated by SIRT5 (156). Proteomic screening of liver extracts from Sirt5 KO mice revealed hyperglutarylation of 683 lysine sites on 191 proteins; more than three quarters of these proteins were found to be mitochondrial (156).…”
Section: Sirt5 and Protein Deacylationsupporting
confidence: 51%
“…Similarly, Rardin et al reported that SIRT5 deficiency resulted in hypersuccinylation of 32% sites in 56% of mitochondrial proteins overall (127). The preference of SIRT5 for negatively charged acyl groups was further corroborated by another recent study (156). Tan et al identified and validated lysine glutarylation as an evolutionary conserved posttranslational modification; similar to lysine succinylation, this modification was also regulated by SIRT5 (156).…”
Section: Sirt5 and Protein Deacylationsupporting
confidence: 48%
See 3 more Smart Citations